PENGARUH CENDAWAN Verticillium lecanii (ZIMM) ISOLAT PALOLO TERHADAP MORTALITAS WALANG SANGIT Leptocorisa acuta Thunberg. (HEMIPTERA: ALYDIDAE) PADA TANAMAN PADI (Oryza sativa L.) - Fitra Jaya Ardi; Flora Pasaru; Burhanuddin Nasir (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
Rice is the raw materials for staple food that are vital to Indonesians. The production of dried unhusked rice (DUR) in Central Sulawesi province in 2014 was 1,022,054 t decreasing 9,310 t (0.90%) compared to the previous production in 2013 (1,031,364 t).  Therice production in 2014 had contributed about 1.44% to the total national DUR production of 70.85 million t (CBS, 2015). The decreasing productivity is partly due to earhead rice bugs. The purpose of the study was to determine the effect of V. lecanii Palolo fungal isolates of different suspension dilutionson the mortality of testedearhead rice bugs(Leptocorisa acuta Thunberg) keptin a house screen.  The propagation of V. lecanii using PSA media and themaking of suspension dilution were carried out in Plant Pest laboratory of Faculty of Agriculture Tadulako University in February to April 2016.  The experiment was arranged in a Completely Randomized design with five treatments i.e. control, dilutions of 10-3, 10-5, 10-7, and 10-9.  Each experimental unit was replicated thrice.  Each treatment of the dilutions was 1 ml drew up using a pipette and allowed to dropdirectly on the ear bug body.  The bugs then were released into the house screen within whichgrown plant rice had reached a milky grain phase.  The mortality of the bugs infected with V. lecanii was observed seven days after the applications.  The highest imago mortality of the earhead rice bugs was found in the 10-5 dilution of Palolo V. lecanii isolates. Keywords: Leptocorisa acuta, Rice and Verticillium lecanii.